Youtube Videos and Snowball Throwing Technique to Improve Students’ Speaking Skill - NABELLA DWI MEILINDA (Edukasi, 2018)
Snowball throwing technique is an interesting strategy which enables students to think and to discuss an issue from different points of view by using the video. This study was done to reveal if (1) there was a significant difference in the eleventh graders’ speaking skill between those who were given intervention by using youtube video with a snowball throwing technique and those who were not, and (2) there was significant difference among good, average, and poor speaking categories among the sample. The participants of this study consisted of 106 eleventh graders of SMA Muhammadiyah 6 Palembang. By means of purposive sampling, 40 students were involved where 20 students of XI. Class IPA 1 was in control group and other 20 students of XI IPA 2 was in experimental group. This study used a quasi-experimental design with non-equivalent pretest and posttest design. To collect the data, speaking test was administered twice as the pretest and posttest for both groups. The result revealed that there was a significant difference in speaking skill between students taught by using youtube video with snowball throwing technique and those who were not. Last, there was a significant difference among good, average, and poor speaking categories among the sample.